Energy Saving Opportunities in 3-Phase Induction Motors with Variable Speed Drive (V.S.D.) Drives - Renanda Nia Rachmadita; Farhan Wahyu Nur Rahman; Edy Setiawan; Anda Iviana Juniani; Wiediartini Wiediartini; Lugas Jagad Satrianata (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2024)
Most of the load in the motorcycles industry is motors. So, the largest energy use is in motorcycles. This study aims to prove the effect of speed change on a three-phase induction motor on energy consumption with a V.S.D. drive. The method used in this proof uses direct experiment methods and data analysis. The relationship between speed and energy use can be demonstrated through testing and data analysis. The results show that V.S.D. is set at frequencies of 20 Hz and 40 Hz to regulate the speed of the motor as a pump drive can save its energy use. This resulted in a reduction in energy consumption of 20.54% and operational costs of up to Rp 3,292.32 per month in the implementation of the motor as a pump driver.